Development of the Conversational Health Literacy Assessment Tool for maternity care (CHAT-maternity-care): participatory action research - Evi M.E. Vlassak; Elina Miteniece; Judit K.J. Keulen; Marjolein Gravendeel; Irene Korstjens; Luc Budé; Marijke J.C. Hendrix; Marianne J. Nieuwenhuijze (BMC, 2024)
Abstract Background Limited health literacy in (expectant) parents is associated with adverse health outcomes. Maternity care providers often experience difficulties assessing (expectant) parents' level of health literacy. The aim was to develop, evaluate, and iteratively adapt a conversational tool that supports maternity care providers in estimating (expectant) parents' health literacy. Methods In this participatory action research study, we developed a conversational tool for estimating the health literacy of (expectant) parents based on the Conversational Health Literacy Assessment Tool for general care, which in turn was based on the Health Literacy Questionnaire. We used a thorough iterative process including different maternity care providers, (expectant) parents, and a panel of experts. This expert panel comprised representatives from knowledge institutions, professional associations, and care providers with whom midwives and maternity care assistants work closely. Testing, evaluation and adjustment took place in consecutive rounds and was conducted in the Netherlands between 2019 and 2022. Results The conversational tool 'CHAT-maternity-care' covers four key domains: (1) supportive relationship with care providers; (2) supportive relationship within parents' personal network; (3) health information access and comprehension; (4) current health behaviour and health promotion. Each domain contains multiple example questions and example observations. Participants contributed to make the example questions and example observations accessible and usable for daily practice. The CHAT-maternity-care supports maternity care providers in estimating (expectant) parents' health literacy during routine conversations with them, increased maternity care providers' awareness of health literacy and helped them to identify where attention is necessary regarding (expectant) parents' health literacy. Conclusions The CHAT-maternity-care is a promising conversational tool to estimate (expectant) parents' health literacy. It covers the relevant constructs of health literacy from both the Conversational Health Literacy Assessment Tool and Health Literacy Questionnaire, applied to maternity care. A preliminary evaluation of the use revealed positive feedback. Further testing and evaluation of the CHAT-maternity-care is required with a larger and more diverse population, including more (expectant) parents, to determine the effectiveness, perceived barriers, and perceived facilitators for implementation.